Smart Emergency Traffic Light System - Shamsudin, Saffi Iswadi; Bakar, Lilywati (Progress in Engineering Application and Technology, 2020)
The aim of this study was to design a smart system on traffic light for emergency purpose. The goal of this study is to facilitate the emergency vehicle go through a busy intersection without causes any new accident due to misunderstanding of all road users. There are several objectives of this study which is provides emergency access for emergency personnel at the traffic light. Next, facilitates the journey of emergency personnel during traffic light and avoids any accidents in traffic lights due to misunderstandings and confusion regarding the siren’s direction of emergency vehicle. The idea of this system by using RFID control that can interrupt the normal sequence of traffic light to change the path that emergency vehicle is travelling on into green after a few second while the other path will be all red. Thus, it may reduce the delay of emergency vehicle travel to a scene or specific place while providing their emergency service to society efficiently. This system includes transmitter (RFID card/tag) and receiver (RFID reader) part to be fully control by a RFID RC522 module. With a certain operating distance, the receiver and transmitter can communicate with each other to enable the green light on the road passed by the emergency vehicle. The transferred data and signals are read wirelessly by the reader before it is finally sent to the processor for next operation.